English Teachers’ Conceptualizations of Key Competencies in English Language Teaching and Challenges to Their Implementation - Lu, Huashan; Jiang, Changgang; Guo, Fei (Frontiers in Psychology, 2022)
In the current literature, limited empirical research exists on the key competencies of front-line English teachers, especially primary and middle school English teachers in rural areas. The present research focuses on front-line teachers and discusses their knowledge of the key competencies of English subjects. This article surveyed eight rural junior middle school English teachers with respect to their awareness regarding the cultivation of students’ key competencies in English subjects through in-depth interviews, as well as the difficulties and challenges they face in curriculum implementation. The study found that although front-line teachers have a positive attitude towards the key competencies of English subjects, there is still a certain gap between their understanding of key competencies and the policy requirements and practical needs. In order to implement core qualities and effectively promote curriculum reform, we should strengthen teacher development training for front-line English teachers, especially primary and secondary school English teachers in rural areas, to enhance their understanding and professionalization of the new round of curriculum reform.